Hubungan Hukum Klausula Arbitrase Dengan Yurisdiksi Pengadilan Negeri - Jeffry Latumahina* (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2020)
ABSTRACTThis research analyzed a Distribution Agreement between Roche Indonesia company (“Roche”) and distributing company Perusahaan Dagang Tempo (“Tempo”) which had an arbitration clause and verdict of South Jakarta District Court in Roche-Tempo case consisted of Putusan No. No.454/Pdt.G/1999/PN.Jak.Sel dated 29 May 2000. In distributing Roche’s pharmaceutical products in Indonesian domestic market, Roche had a distribution agreement with Tempo as its sole distributor. During the contract period, Roche terminated part of the contract unilaterally, which suffered Tempo. Tempo then filed a lawsuit against Roche to South Jakarta District Court, which was then rejected by Roche, claiming that the District Court had no jurisdiction over the case since the Distribution Agreement had an arbitration clause stipulating that any dispute must be settled arbitration, not the court. This Research was aimed to observe and to analyze the legal forces and the existences of arbitration clause in the Distribution Agreement viewed from Law No.30 of 1999 on Arbitration and Alternative Dispute Resolution (“Arbitration Law”). The research was also to find out whether or not the consideration of the Judge in deciding a dispute of an agreement which involves arbitration clause was in accordance with Arbitration Law. This research applies juridical normative approach with the specification of analysis descriptive research, as well as qualitative normative data analysis method. This research showed that the arbitration clause in the Distribution Agreement had a legal force and binding capacity over Tempo and Roche. Tempo’s denial of this clause by filing the case to the district court was clearly inappropriate and dishonor the agreement. As for the South Jakarta District Court, which claimed that it had jurisdiction over this case was not in accordance with Arbitration Law.  Keywords: Arbitration Clause; Distribution Agreement; Court Jurisdiction; Roche; Tempo